Economic returns to Communist Party membership: evidence from urban Chinese twins - Hongbin Li; Pak Wai Liu; Junsen Zhang; Ning Ma (Institute for the Study of Labor (IZA), 2006)
This paper estimates the returns to membership of the Chinese Communist Party using unique twins data we collected from China. Our OLS estimate shows that being a Party member increases earnings by 10%, but the within-twin-pair estimate becomes zero. One interpretation of these results is that the OLS Party premium is due to omitted ability and family background. This interpretation would suggest that Party members fare well not because of their special political status per se, but because of the superior ability that made them Party members. The estimates are also consistent with an alternative interpretation that Party membership not only has its own effect but also has an external effect on the sibling.
Keywords: J31; O15; P26; 330; twins; communist party membership; China; Politische Partei; Mitgliedschaft; Einkommen; Familie; China